Paleo-environments of sedimentation, mud volcanism and hydrocarbons migration in the South-Caspian basin - Yusubov, N. P.; Guliev, I. S.; Guseinova, Sh. M. (Geofizicheskiy Zhurnal, 2020)
One of the problems of oil and gas geology, not finally solved, is a mechanism of hydrocarbons migration and oil and gas deposits formation. It is well known that for production of deposits the presence of not only parent rocks, rocks-collectors and roof-rocks is required but also migration ways available for transporting hydrocarbons formed into parent rocks to previously formed traps. Results of most recent studies based on complex geological interpretation of data of 2D/3D seismic exploration and commercial geophysics are given in the paper that allowed to reveal the mechanism of mud volcanic activity formation which is, according to authors opinion, the cause of hydrocarbon migration from oil and gas parent rocks to rocks collectors with mud volcano channels considered as the principal ways of migration. The authors consider that geodynamic processes related to tangential compression of the whole basin and the mud volcanism continued up to now produce favorable conditions for primary hydrocarbon migration from oil and gas parent rocks to eruptive channels of mud volcanoes and secondary migration to reservoir beds. It has been revealed that productive stratum of the Lower Pliocene is an aggregate of bodies different by their shape and lithological composition built by river paleo-channels isolated from each other hydraulically and the Pliocene structures with amplitudes up to 500 m are separated by deep geosynclines which block horizontal migration of fluids. It has been found that at the depths corresponding to oil and gas-bearing horizons of productive stratum there is no system of faults and fissures with capability for vertical migration of fluids from oil and gas parent rocks to rocks collectors. Therefore, mud volcanism is the most probable mechanism regulating the vertical migration of HC.